Changes in the content of progesterone, insulin and cortisol in treatment course of pregnant women with the threat of preterm labor in chronic stress conditions - Shevchenko, A. O. (Zaporozhye Medical Journal, 2018)
Despite the fact that many national and foreign scientific groups are working to address the issue of preterm labor, the rate of miscarriage ranges from 5.0 to 10.0 % without decreasing trend. The aim: to determine the efficacy of progesterone and thiotriazoline combination in the risk of premature birth on the basis of studying the hormonal profile dynamics and perinatal consequences. Materials and methods. Serum progesterone levels as the main hormone of pregnancy, insulin, cortisol were measured in pregnant women with the threat of preterm labor (TPL) and in the umbilical cord blood; insulin-cortisol index was calculated. Pregnant women were divided into two groups: 1 - basic (n = 22), and 2 – comparison group (n = 22). For hormonal disorders correction and pregnancy prolongation patients of basic group with TPL at 22–34 weeks of gestation received preparations of progesterone and thiatriazoline: natural micronized progesterone vaginal suppositories, 100 mg, twice-daily and0.2 g of thiatriazoline rectal suppositories 1 time per day for 10 days. Comparison group patients at the 22–34 weeks of gestation received standard treatment according to approved clinical protocols. Results: Analysis of the progesterone, cortisol and insulin blood serum baseline levels of both pregnant women study groups showed no significant difference. In the basic group the progesterone level during 10 days of treatment decreased from 162.5 ng / ml to 148.8 ng / ml (P > 0.05). There was no significant difference between the progesterone contents before and after treatment in both groups. In pregnant women the insulin level increased from 15.9 μMe / ml to 34.7 μMe / ml (P < 0.05). In the comparison group the insulin level also increased from 13.9 μMe / ml to 14.4 μMe / ml, but not significantly. The cortisol level in the basic group insignificantly increased from 564.6 ng / ml to 600.5 ng / ml (P > 0.05). In the comparison group the cortisol level before and after treatment did not change significantly – 536.6 ± 321.6 ng / ml and 546.5 ± 334.2 ng / ml, respectively. There was a significant increase in insulin / cortisol index from 0.027 U.M. to 0.066 U.M. (P < 0.05) in the pregnant women of the basic group after 10 days of treatment. The baseline level of insulin / cortisol index in pregnant women of comparison group, as in the basic group, was 0.027 U.M. After a week of standard therapy it significantly increased up to 0.033 U.M. (P < 0.05). There was no significant difference in the progesterone level in the umbilical cord blood of both study groups (1 – 1483 ng / ml, 2 – 1662 ng / ml). Insulin content in the umbilical cord blood in the basic group was the lowest (3.78 μMe / ml) and significantly differed from that of comparison group (4.29 μMe / ml) (P < 0.05). The levels of cortisol in the umbilical cord blood did not differ between women of the basic and comparison groups – 264.5 ng / ml versus 305.2 ng / ml. The insulin-cortisol index in all groups was not significantly different. Conclusions. In women with a risk of preterm birth the decrease in insulin and cortisol levels in the umbilical cord blood indicates the physiological adaptation to stress factors during pregnancy and the therapeutic strategy chosen effectiveness. The use of micronized progesterone in combination with antioxidants increases the stress hormonal index in the basic group by 2.5 times, indicating the proposed treatment regimen effectiveness and preventing premature birth.